Children's and adolescents' descriptors of asthma symptoms: An integrative review - Tanya Wallace-Farquharson; Hyekyun Rhee; Laurie Duckworth; Jennifer Harrison Elder; Diana J. Wilkie (Elsevier, 2022)
Background: Accurate assessment of asthma symptoms is central to appropriate treatment and management; however effective communication about symptoms−how it is perceived and reported−remain challenging in pediatric clinical and research settings. Objective: To synthesize the existing pediatric literature on children's and adolescents' word descriptors of asthma symptoms. Methods: In this integrative review, we systematically searched Cumulative Index of Nursing and Allied Health Literature and PubMed databases to identify original research studies from 1980 to 2021 on children and adolescents' word descriptors of asthma symptoms. Results: The search yielded 2,232 articles, of which 21 studies met the eligibility criteria. Scientific literature focused on children and adolescents' descriptions of asthma symptoms are limited. In addition to standard asthma symptom terminology (e.g. cough, wheeze, chest tightness, shortness of breath), pediatric populations used nonstandard word choices to describe the asthma symptom experience. Children and adolescents used a variety of affective (e.g. 'helpless', 'afraid of dying') and sensory words (e.g. 'pressure in chest', 'tightness, lungs feel shut') to describe the phenomena. Literature examining race differences in word descriptors in pediatrics is limited; thus it is unclear if word descriptors vary by race or ethnicity. Evidence of relationships between descriptors and gender and age are also lacking. Conclusions: Our review elucidates gaps in the literature regarding the full extent of the language common to racially and ethnically diverse samples of children and adolescents. Further research is warranted to help clinicians and researchers query children and adolescents' experience of asthma symptoms.